2009
DOI: 10.1901/jeab.2009.92-257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differing Response‐force Requirements on Food‐maintained Responding in C57bl/6j Mice

Abstract: The effect of force requirements on response effort was examined using inbred C57BL/6J mice trained to press a disk with their snout. Lateral peak forces greater than 2 g were defined as responses (i.e., all responses above the measurement threshold). Different, higher force requirements were used to define criterion responses (a subclass of all responses) that exceeded the requirement and produced a reinforcer. The reinforcer was sweetened, condensed milk, delivered upon response termination. All mice were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…Interestingly, no effect of workload on overall response rate was detected. This result is inconsistent with many reports indicating an inverse relationship between force requirements and response rate (Adair & Wright, 1976; Alling & Poling, 1995; Bradshaw, Szabadi & Ruddle, 1983; Chung, 1965; Posadas‐Sanchez, 2005), although support for this relationship is not unequivocal (Collier & Jennings, 1969; Elsmore & Brownstein, 1968; Stanley & Aamodt, 1954; Zarcone, Chen & Fowler, 2007, 2009). Nonetheless, overall response rate is a crude measure of performance: By collapsing all the IRTs into the denominator, response rates neglect the information contained in the distribution of IRTs.…”
Section: Discussion Phase 1: Maintenancecontrasting
confidence: 77%
“…Interestingly, no effect of workload on overall response rate was detected. This result is inconsistent with many reports indicating an inverse relationship between force requirements and response rate (Adair & Wright, 1976; Alling & Poling, 1995; Bradshaw, Szabadi & Ruddle, 1983; Chung, 1965; Posadas‐Sanchez, 2005), although support for this relationship is not unequivocal (Collier & Jennings, 1969; Elsmore & Brownstein, 1968; Stanley & Aamodt, 1954; Zarcone, Chen & Fowler, 2007, 2009). Nonetheless, overall response rate is a crude measure of performance: By collapsing all the IRTs into the denominator, response rates neglect the information contained in the distribution of IRTs.…”
Section: Discussion Phase 1: Maintenancecontrasting
confidence: 77%
“…Responses counted at one point in a study are not counted at other points, and apparent rate decreases observed when force requirements are increased are likely because a portion of the original response class goes unmeasured. When the subcriterion responses are measured by defining a constant threshold, a consistent response definition is maintained, and we typically observed rate increases following increased force requirements, replicating the results of others (Mintz et al, ; Zarcone et al, , ). Our data underscore the importance of measuring subcriterion responses when force criteria are changed (Notterman & Mintz, ; Walker, Faustman, Fowler, & Kazar, ; Zarcone et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Zarcone et al () went on to conclude that apparent punishment effects observed under increased force requirements may be due to the definitional changes in the operant that arise when levers are used to define force criteria. Zarcone, Chen, and Fowler () replicated their prior study with a different mouse strain, C57Bl/6 J, and found again that increased force requirements increase operant behavior.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…As any grocer will tell you, changing the unit price of a reinforcer may be accomplished by either increasing the cost of obtaining the reinforcer or decreasing the benefits of the reinforcer (e.g., selling an ounce less dried pasta at the same price). In the laboratory, cost is typically quantified by the number of responses the subject must emit per reinforcer, but it could also be quantified as effort expended per reinforcer (e.g., time integral of force; Zarcone, Chen, & Fowler, 2009), time to a reinforcer (e.g., Tsunematsu, 2000), or a commodity loss after each response (e.g., a responsecost contingency), to name just a few cost dimensions. For humans, the cost component may also be specified as the amount of money paid per reinforcer (money being a medium by which past labor is exchanged for present goods and services).…”
Section: Consumer Demandmentioning
confidence: 99%